Zinc battery electrolyte and zinc battery

JP7630918B2Active Publication Date: 2025-02-18ENERGYWITH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020085165
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-05-14
Publication Date
2025-02-18
Estimated Expiration
2040-05-14

AI Technical Summary

Benefits of technology

【0011】 本発明の一側面によれば、亜鉛電池を保存したときの放電容量の低下を抑制することが可能な亜鉛電池用電解液を提供することができる。本発明の他の一側面によれば、当該亜鉛電池用電解液を備える亜鉛電池を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007630918000001
    Figure 0007630918000001
Patent Text Reader

Abstract

To provide an electrolytic solution for a zinc battery capable of suppressing the decrease in discharge capacity when the zinc battery is stored, and also to provide the zinc battery equipped with the electrolytic solution for the zinc battery.SOLUTION: An electrolytic solution for a zinc-battery contains an alkali metal hydroxide, a surfactant and an organic compound containing an oxygen atom. The zinc battery includes: a positive electrode, a negative electrode, and the electrolytic solution for the zinc battery.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrolyte for a zinc battery and a zinc battery. [Background technology]

[0002] Known zinc batteries include nickel-zinc batteries, air-zinc batteries, and silver-zinc batteries. For example, nickel-zinc batteries are aqueous batteries that use an aqueous electrolyte such as an aqueous potassium hydroxide solution, and therefore are highly safe. In addition, the combination of zinc electrodes and nickel electrodes is known to provide a high electromotive force for an aqueous battery. Furthermore, nickel-zinc batteries have excellent input / output performance and low cost, and therefore their applicability to industrial applications (e.g., backup power sources, etc.) and automotive applications (e.g., hybrid vehicles, etc.) is being considered.

[0003] The charge and discharge reactions of a nickel-zinc battery proceed, for example, according to the following formula (discharge reaction: to the right, charge reaction: to the left). (Positive electrode)2NiOOH+2H2O+2e - → 2Ni(OH)2+2OH - (Negative electrode) Zn+2OH - → Zn(OH)2+2e -

[0004] As shown in the above formula, in zinc batteries, zinc hydroxide (Zn(OH)2) is produced by the discharge reaction. Zinc hydroxide is soluble in the electrolyte, and when zinc hydroxide dissolves in the electrolyte, it becomes zinc tetrahydroxide ions ([Zn(OH)4] 2-) diffuses into the electrolyte. As a result, the negative electrode undergoes a morphological change (deformation) and the distribution of the charging current becomes uneven, causing zinc to precipitate locally on the negative electrode, resulting in the formation of dendrites (branched crystals). In conventional zinc batteries, when dendrites grow due to repeated charging and discharging, the dendrites may penetrate the separator and cause a short circuit. For this reason, various attempts have been made to prevent such short circuits caused by dendrites and to improve the life performance. For example, the following Patent Document 1 discloses a nickel-zinc battery in which a nonwoven fabric made of nylon, polypropylene, or the like is nickel-plated and the nonwoven fabric is interposed between the positive and negative electrodes. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 58-126665 Summary of the Invention [Problem to be solved by the invention]

[0006] For zinc batteries, in addition to improving the life performance, it is required to suppress the decrease in discharge capacity during storage.

[0007] An object of the present invention is to provide an electrolyte for a zinc battery capable of suppressing a decrease in discharge capacity during storage of the zinc battery.An object of the present invention is to provide a zinc battery comprising the electrolyte for a zinc battery. [Means for solving the problem]

[0008] One aspect of the present invention provides an electrolyte for a zinc battery, comprising an alkali metal hydroxide, a surfactant, and an organic compound containing an oxygen atom.

[0009] Another aspect of the present invention provides a zinc battery comprising a positive electrode, a negative electrode, and the above-mentioned zinc battery electrolyte.

[0010] According to the above-mentioned zinc battery electrolyte and zinc battery, the decrease in discharge capacity during storage of the zinc battery can be suppressed. Effect of the Invention

[0011] According to one aspect of the present invention, it is possible to provide an electrolyte for a zinc battery capable of suppressing a decrease in discharge capacity during storage of the zinc battery. According to another aspect of the present invention, it is possible to provide a zinc battery including the electrolyte for a zinc battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] In this specification, the numerical range indicated by "~" indicates a range including the numerical values ​​described before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a numerical range of a certain stage can be arbitrarily combined with the upper limit or lower limit of a numerical range of another stage. In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in an experimental example. "A or B" may include either A or B, or may include both. Unless otherwise specified, the materials exemplified in this specification may be used alone or in combination of two or more types. In this specification, the amount of each component used in the composition means the total amount of the multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified. In this specification, the term "film" or "layer" includes a structure having a shape formed on the entire surface when observed as a plan view, as well as a structure having a shape formed on a part of the surface. In this specification, the term "process" refers not only to an independent process, but also to a process that cannot be clearly distinguished from other processes, as long as the intended effect of the process is achieved.

[0013] Hereinafter, the embodiments of the present invention will be described in detail. However, the present invention is not limited to the following embodiments, and various modifications can be made within the scope of the present invention.

[0014] The zinc battery electrolyte according to the present embodiment (hereinafter, sometimes simply referred to as "electrolyte") is used as an electrolyte for a zinc battery (e.g., a zinc secondary battery). The zinc battery according to the present embodiment includes a positive electrode, a negative electrode, and the electrolyte according to the present embodiment. The zinc battery may include a zinc electrode as the negative electrode. Examples of zinc batteries include nickel-zinc batteries (e.g., nickel-zinc secondary batteries) in which the positive electrode is a nickel electrode; air-zinc batteries (e.g., air-zinc secondary batteries) in which the positive electrode is an air electrode; and silver-zinc batteries (e.g., silver-zinc secondary batteries) in which the positive electrode is a silver oxide electrode.

[0015] The electrolyte according to the present embodiment contains an alkali metal hydroxide, a surfactant, and an organic compound containing oxygen atoms.The electrolyte according to the present embodiment can suppress the decrease in discharge capacity when zinc battery is stored, and can reduce the change rate of discharge capacity before and after storage when zinc battery is stored at 40°C for 28 days and then charged and discharged.

[0016] The factors that can provide such an effect include, but are not limited to, the following factors. That is, the coexistence of an alkali metal hydroxide (M-OH, where M represents an alkali metal element) and an organic compound containing an oxygen atom (R-OH) causes an equilibrium reaction "M + -OH - + RO - H + ⇔ RO - K + + H2O" is produced. This prevents the alkali metal hydroxide from ionizing (dissociating) into alkali metal cations and hydroxide ions, thereby preventing the electrolyte from becoming excessively basic. The surfactant also forms a coating on the surface of the zinc in the electrode material. As a result of these synergistic effects, when a zinc battery is stored, the zinc in the electrode material is oxidized to produce zinc oxide, which prevents the formation of a passive state on the surface of the electrode material. This prevents the decrease in discharge capacity when the zinc battery is stored.

[0017] According to the electrolyte of the present embodiment, it is possible to obtain excellent high-rate discharge performance in a zinc battery. For example, according to the electrolyte of the present embodiment, it is possible to suppress a decrease in the initial discharge capacity when discharged at a constant current of 10 C compared to the initial discharge capacity when discharged at a constant current of 0.2 C.

[0018] The unit "C" is a relative expression of the magnitude of the current when discharging the rated capacity at a constant current from a fully charged state. The unit "C" means "discharge current value (A) / battery capacity (Ah)". For example, the current that can discharge the rated capacity in 1 hour is expressed as "1C", and the current that can discharge the rated capacity in 2 hours is expressed as "0.5C".

[0019] Examples of the alkali metal hydroxide include potassium hydroxide (KOH), sodium hydroxide (NaOH), and lithium hydroxide (LiOH). The alkali metal hydroxide may be ionized (dissociated) in an aqueous solution, and may exist as a salt. From the viewpoint of easily suppressing the decrease in discharge capacity during storage of the zinc battery and easily obtaining excellent high-rate discharge performance, the alkali metal hydroxide preferably contains at least one selected from the group consisting of potassium hydroxide and lithium hydroxide, and more preferably contains potassium hydroxide.

[0020] The content of alkali metal hydroxide in the electrolyte (total amount of alkali metal hydroxide) is preferably within the following range based on the total amount of the electrolyte, from the viewpoint of easily suppressing the decrease in discharge capacity during storage of the zinc battery and from the viewpoint of easily obtaining excellent high-rate discharge performance. The content of alkali metal hydroxide is preferably 10 mass% or more, 15 mass% or more, 20 mass% or more, 25 mass% or more, or 30 mass% or more. The content of alkali metal hydroxide is preferably 50 mass% or less, 45 mass% or less, 40 mass% or less, or 35 mass% or less. From these viewpoints, the content of alkali metal hydroxide is preferably 10 to 50 mass%.

[0021] The content of potassium hydroxide in the electrolyte is preferably in the following range based on the total amount of the electrolyte, from the viewpoint of easily suppressing the decrease in discharge capacity during storage of the zinc battery and from the viewpoint of easily obtaining excellent high-rate discharge performance. The content of potassium hydroxide is preferably 10 mass% or more, 15 mass% or more, 20 mass% or more, 25 mass% or more, or 30 mass% or more. The content of potassium hydroxide is preferably 50 mass% or less, 45 mass% or less, 40 mass% or less, or 35 mass% or less. From these viewpoints, the content of potassium hydroxide is preferably 10 to 50 mass%.

[0022] The content of lithium hydroxide in the electrolyte is preferably in the following range based on the total amount of the electrolyte, from the viewpoint of easily suppressing the decrease in discharge capacity during storage of the zinc battery and from the viewpoint of easily obtaining excellent high-rate discharge performance. The content of lithium hydroxide is preferably 0.1 mass% or more, 0.3 mass% or more, 0.5 mass% or more, 0.8 mass% or more, or 1 mass% or more. The content of lithium hydroxide is preferably 3 mass% or less, 2 mass% or less, 1.5 mass% or less, or 1.2 mass% or less. From these viewpoints, the content of lithium hydroxide is preferably 0.1 to 3 mass%.

[0023] The electrolyte according to the present embodiment contains a surfactant. Examples of the surfactant include a nonionic surfactant (nonionic surfactant), an anionic surfactant, a cationic surfactant, and an amphoteric surfactant. From the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance, the surfactant preferably contains at least one selected from the group consisting of a nonionic surfactant, an anionic surfactant, and a cationic surfactant. The surfactant is preferably an embodiment containing a nonionic surfactant, preferably an embodiment containing an anionic surfactant, and preferably an embodiment containing a cationic surfactant. From the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored, the surfactant preferably contains at least two selected from the group consisting of a nonionic surfactant, an anionic surfactant, and a cationic surfactant.

[0024] The nonionic surfactant has a nonionic hydrophilic group and a hydrophobic group. Examples of the nonionic surfactant include polyoxyethylene-containing ester compounds such as polyoxyethylene fatty acid esters, polyoxyethylene sorbitan fatty acid esters, and polyoxyethylene sorbitol fatty acid esters; and polyoxyethylene-containing ether compounds such as polyoxyethylene alkyl ethers and polyoxyethylene alkyl phenyl ethers. From the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance, the nonionic surfactant preferably contains at least one selected from the group consisting of polyoxyethylene alkyl ethers and polyoxyethylene alkyl phenyl ethers, and more preferably contains polyoxyethylene alkyl phenyl ethers.

[0025] The polyoxyethylene alkyl ether has, for example, a structure represented by the following general formula (1a). R 1a O(CH2CH2O) m1 H …(1a) [In formula (1a), m1 is an integer of 2 to 60, and R 1a is a hydrocarbon group having 1 to 30 carbon atoms.

[0026] Polyoxyethylene alkylphenyl ether has, for example, a structure represented by the following general formula (1b). R 1b C6H4O(CH2CH2O) m2 H …(1b) [In formula (1b), m2 is an integer of 2 to 60, and R 1b is a hydrocarbon group having 1 to 30 carbon atoms.

[0027] R 1a and R 1b The hydrocarbon group of R may be linear or branched, and may be saturated or unsaturated. 1a and R 1b The hydrocarbon group of R is preferably an alkyl group. 1aThe number of carbon atoms in the hydrocarbon group is preferably 10 to 18. 1b The number of carbon atoms in the hydrocarbon group is preferably 4 to 12, more preferably 6 to 10, and further preferably 8. m1 and m2 each represent an average degree of polymerization, which is preferably 5 to 12, and more preferably 7 to 10.

[0028] Specific examples of polyoxyethylene alkyl ethers include polyoxyethylene decyl ether, polyoxyethylene undecyl ether, polyoxyethylene dodecyl ether, polyoxyethylene tridecyl ether, polyoxyethylene tetradecyl ether, polyoxyethylene pentadecyl ether, polyoxyethylene hexadecyl ether, polyoxyethylene heptadecyl ether, and polyoxyethylene octadecyl ether.

[0029] Specific examples of polyoxyethylene alkylphenyl ethers include polyoxyethylene octylphenyl ether and polyoxyethylene nonylphenyl ether.

[0030] The anionic surfactant has an anionic hydrophilic group and a hydrophobic group. Examples of the anionic surfactant include polyoxyalkylene alkyl ether phosphate (e.g., polyoxyethylene alkyl ether phosphate), polyoxyethylene alkyl ether sulfate, sodium dodecylbenzene sulfonate, alkali salt of styrene-acrylic acid copolymer, sodium alkyl naphthalene sulfonate, sodium alkyl diphenyl ether disulfonate, monoethanolamine lauryl sulfate, triethanolamine lauryl sulfate, ammonium lauryl sulfate, monoethanolamine stearate, sodium stearate, sodium lauryl sulfate, monoethanolamine of styrene-acrylic acid copolymer, and the like. The anionic surfactant preferably contains polyoxyalkylene alkyl ether phosphate, more preferably contains polyoxyethylene alkyl ether phosphate, from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance.

[0031] The cationic surfactant has a cationic hydrophilic group and a hydrophobic group. Examples of the cationic surfactant include aliphatic amines or their salts, alkylamidoamine salts, monoalkyltrimethylammonium salts, dialkyldimethylammonium salts, alkylbenzyldimethylammonium salts, alkylpyridinium salts, benzethonium chloride salts, and other quaternary ammonium salt-type cationic surfactants. From the viewpoint of easily suppressing the decrease in discharge capacity during storage of the zinc battery and from the viewpoint of easily obtaining excellent high-rate discharge performance, the cationic surfactant preferably contains at least one selected from the group consisting of monoalkyltrimethylammonium salts and dialkyldimethylammonium salts, and more preferably contains monoalkyltrimethylammonium salts.

[0032] The monoalkyltrimethylammonium salt and the dialkyldimethylammonium salt have, for example, a structure represented by the following general formula (2). (R 2a ) n N + (R 2b ) 4-n X - …(2) [In formula (2), n is 1 or 2, and R 2a and R 2b are each independently a hydrocarbon group having 1 to 20 carbon atoms; - is an anion. When n is 2, multiple R 2a may be the same or different. 2b may be the same or different.

[0033] R 2a The hydrocarbon group of R may be linear or branched, may be saturated or unsaturated, and may contain a cyclic structure such as an alicyclic structure. 2a The hydrocarbon group of R is preferably an alkyl group. 2a The number of carbon atoms in the hydrocarbon group is preferably 12 to 18, and more preferably 14 to 16.2b The hydrocarbon group of R may be linear or branched, and may be saturated or unsaturated. 2b The hydrocarbon group of R is preferably an alkyl group. 2b The carbon number of the hydrocarbon group is preferably 1 to 4, and more preferably 1, 2 or 3. - is an anion capable of forming a salt with the quaternary ammonium ion of formula (2), for example, F - , Cl - , Br - , I - Halide ions such as CH3COO - etc. carboxylate ions; sulfate ions; phosphate ions, etc.

[0034] Specific examples of monoalkyltrimethylammonium salts include dodecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, tridecyltrimethylammonium bromide, tridecyltrimethylammonium chloride, tetradecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride, pentadecyltrimethylammonium bromide, pentadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, heptadecyltrimethylammonium bromide, heptadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide, and octadecyltrimethylammonium chloride.

[0035] Specific examples of dialkyldimethylammonium salts include didodecyldimethylammonium bromide, didodecyldimethylammonium chloride, ditridecyldimethylammonium bromide, ditridecyldimethylammonium chloride, ditetradecyldimethylammonium bromide, ditetradecyldimethylammonium chloride, dipentadecyldimethylammonium bromide, dipentadecyldimethylammonium chloride, dihexadecyldimethylammonium bromide, dihexadecyldimethylammonium chloride, diheptadecyldimethylammonium bromide, diheptadecyldimethylammonium chloride, dioctadecyldimethylammonium bromide, and dioctadecyldimethylammonium chloride.

[0036] When the surfactant contains a nonionic surfactant, an anionic surfactant, or a cationic surfactant, the content of the nonionic surfactant, anionic surfactant, or cationic surfactant in the surfactant is preferably 50 mass% or more, 70 mass% or more, 90 mass% or more, 95 mass% or more, 97 mass% or more, or 99 mass% or more based on the surfactant content (total amount of surfactants) from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance. The surfactant may be substantially composed of a nonionic surfactant, an anionic surfactant, or a cationic surfactant (an embodiment in which substantially 100 mass% of the surfactant is a nonionic surfactant, an anionic surfactant, or a cationic surfactant).

[0037] When the surfactant contains a nonionic surfactant and an anionic surfactant, the mass ratio of the content of the anionic surfactant to the content of the nonionic surfactant (content of the anionic surfactant / content of the nonionic surfactant) is preferably in the following range from the viewpoint of easily suppressing the decrease in discharge capacity during storage of the zinc battery and from the viewpoint of easily obtaining excellent high-rate discharge performance. The mass ratio is preferably 0.1 or more, 0.3 or more, 0.5 or more, 0.7 or more, or 1 or more. The mass ratio is preferably 3 or less, 2.5 or less, 2 or less, 1.5 or less, 1.2 or less, or 1 or less. From these viewpoints, the mass ratio is preferably 0.1 to 3.

[0038] When the surfactant contains a nonionic surfactant and a cationic surfactant, the mass ratio of the content of the cationic surfactant to the content of the nonionic surfactant (content of the cationic surfactant / content of the nonionic surfactant) is preferably in the following range from the viewpoint of easily suppressing the decrease in discharge capacity during storage of the zinc battery and from the viewpoint of easily obtaining excellent high-rate discharge performance. The mass ratio is preferably 0.1 or more, 0.3 or more, 0.5 or more, 0.7 or more, or 1 or more. The mass ratio is preferably 3 or less, 2.5 or less, 2 or less, 1.5 or less, 1.2 or less, or 1 or less. From these viewpoints, the mass ratio is preferably 0.1 to 3.

[0039] The content of the surfactant in the electrolytic solution (total amount of the surfactant) is preferably in the following range based on the total amount of the electrolytic solution. The content of the surfactant is preferably 0.0001 mass% or more, 0.0005 mass% or more, 0.001 mass% or more, 0.003 mass% or more, or 0.005 mass% or more from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance. The content of the surfactant is preferably 0.1 mass% or less, 0.08 mass% or less, 0.05 mass% or less, 0.03 mass% or less, or 0.01 mass% or less from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance. From these viewpoints, the content of the surfactant is preferably 0.0001 to 0.1 mass%. The content of the surfactant is preferably 0.008 mass% or more, or 0.01 mass% or more from the viewpoint of easily obtaining even more excellent high-rate discharge performance.

[0040] When the surfactant contains a nonionic surfactant, an anionic surfactant, or a cationic surfactant, the content of the nonionic surfactant, the content of the anionic surfactant, or the content of the cationic surfactant in the electrolyte is preferably in the following range based on the total amount of the electrolyte, from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored, and from the viewpoint of easily obtaining excellent high-rate discharge performance. The content is preferably 0.0001 mass% or more, 0.0005 mass% or more, 0.001 mass% or more, 0.003 mass% or more, or 0.005 mass% or more. The content is preferably 0.1 mass% or less, 0.08 mass% or less, 0.05 mass% or less, 0.03 mass% or less, 0.01 mass% or less, 0.008 mass% or less, or 0.005 mass% or less. From these viewpoints, the content is preferably 0.0001 to 0.1 mass%.

[0041] The electrolyte according to the present embodiment contains an organic compound containing an oxygen atom (excluding compounds corresponding to alkali metal hydroxides or surfactants. Hereinafter, sometimes referred to as "oxygen-containing compound"). The oxygen-containing compound may have a functional group containing an oxygen atom. Examples of the functional group containing an oxygen atom include a carboxyl group, a carboxylate group, a hydroxyl group (excluding OH structures included in a carboxyl group), an epoxy group, an ether group, an alkoxide group, an ester group, a ketone group, and an aldehyde group. From the viewpoint of easily suppressing the decrease in discharge capacity during storage of a zinc battery and easily obtaining excellent high-rate discharge performance, it is preferable that the oxygen-containing compound has at least one selected from the group consisting of a carboxyl group, a carboxylate group, a hydroxyl group, an epoxy group, and an ether group.

[0042] When the oxygen-containing compound has an OH structure, the ratio of the number of OH structures to the number of carbon atoms in the oxygen-containing compound (number of OH structures / number of carbon atoms) is preferably within the following range from the viewpoint of easily suppressing the decrease in discharge capacity during storage of the zinc battery and easily obtaining excellent high-rate discharge performance. The ratio is preferably 0.01 or more, 0.03 or more, 0.05 or more, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, or 5 / 6 or more. The ratio is preferably 2 or less, 1.5 or less, 1.2 or less, 1 or less, 0.9 or less, or 5 / 6 or less. The oxygen-containing compound does not have to have an OH structure.

[0043] From the viewpoint of easily suppressing the decrease in discharge capacity during storage of the zinc battery and easily obtaining excellent high-rate discharge performance, it is preferable that the oxygen-containing compound contains at least one selected from the group consisting of sugars, carboxylic acids (excluding compounds corresponding to sugars), carboxylates (excluding compounds corresponding to sugars), epoxy compounds (compounds having an epoxy group; excluding compounds corresponding to sugars, carboxylic acids, or carboxylates), and ether compounds (compounds having an ether group; excluding compounds corresponding to sugars, carboxylic acids, carboxylates, or epoxy compounds).

[0044] The saccharides may be monosaccharides, disaccharides, trisaccharides, polysaccharides (excluding saccharides corresponding to disaccharides or trisaccharides), etc. Examples of monosaccharides include glucose, fructose, galactose, arabinose, ribose, mannose, xylose, sorbose, rhamnose, fucose, ribodesose, etc. Examples of disaccharides include maltose, trehalose, sucrose, cellobiose, gentiobiose, lactose, melibiose, etc. Examples of trisaccharides include raffinose, gentianose, melezitose, etc. Examples of polysaccharides include cyclodextrin (e.g., γ-cyclodextrin), stachyose, etc. The oxygen-containing compound preferably contains at least one selected from the group consisting of glucose, maltose, and raffinose, from the viewpoint of easily suppressing the decrease in discharge capacity during storage of the zinc battery and easily obtaining excellent high-rate discharge performance.

[0045] Examples of the carboxylic acid include terephthalic acid, isophthalic acid, phthalic acid, benzoic acid, salicylic acid, 3,4,5-trihydroxybenzoic acid, benzenehexacarboxylic acid, formic acid, acetic acid, propionic acid, butyric acid, valeric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, aconitic acid, pyruvic acid, oxaloacetic acid, glycidyl formate, glycidyl acetate, and glycidyl benzoate. Examples of the carboxylate include salts of these carboxylic acids. Examples of the carboxylate include alkali metal salts such as sodium salts (e.g., disodium terephthalate) and potassium salts. The carboxylate preferably contains an alkali metal salt, and more preferably contains a sodium salt, from the viewpoint of easily suppressing the decrease in discharge capacity during storage of the zinc battery and easily obtaining excellent high-rate discharge performance. From the viewpoint of easily suppressing the decrease in discharge capacity during storage of a zinc battery and easily obtaining excellent high-rate discharge performance, the oxygen-containing compound preferably contains at least one selected from the group consisting of carboxylic acids having aromatic rings and carboxylates having aromatic rings, more preferably contains at least one selected from the group consisting of terephthalic acid and terephthalic acid salts, and even more preferably contains at least one selected from the group consisting of terephthalic acid and sodium salts of terephthalic acid.

[0046] The number of carboxyl groups in the carboxylic acid or the number of carboxylate salts in the carboxylate is 1 or more, and from the viewpoint of easily suppressing a decrease in discharge capacity during storage of the zinc battery and easily obtaining excellent high-rate discharge performance, the following ranges are preferable: The number of carboxyl groups or carboxylate salts is preferably 2 or more; The number of carboxyl groups or carboxylate salts is preferably 4 or less, 3 or less, or 2 or less.

[0047] Examples of the epoxy compound include monofunctional epoxy compounds and polyfunctional epoxy compounds. Examples of the monofunctional epoxy compound include 1,2-epoxyethane, 1,2-epoxypropane, 1,2-epoxybutane, 1,2-epoxy-2-methylpropane, 1-phenyl-1,2-epoxyethane, epichlorohydrin, epibromohydrin, glycidyl methyl ether, allyl glycidyl ether, polyethylene oxide glycidyl ether, glycidyl amide, butyl glycidyl ether, 2-ethylhexyl glycidyl ether, stearyl glycidyl ether, lauryl glycidyl ether, butoxy polyethylene glycol glycidyl ether, phenol polyethylene glycol glycidyl ether, allyl glycidyl ether, phenyl glycidyl ether, p-methylphenyl glycidyl ether, p-ethylphenyl glycidyl ether, p-sec-butylphenyl glycidyl ether, p-tert-butylphenyl glycidyl, glycidyl acrylate, and glycidyl methacrylate. Examples of the polyfunctional epoxy compound include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, phenol novolac type epoxy compounds, cresol novolac type epoxy compounds, polyphenol type epoxy compounds, cyclic aliphatic epoxy compounds, aliphatic glycidyl ether type epoxy compounds, glycidyl ester type epoxy compounds, glycidyl diamine type epoxy compounds, heterocyclic epoxy compounds, cyclic aliphatic epoxy compounds, etc. The oxygen-containing compound preferably contains a monofunctional epoxy compound, more preferably contains 1,2-epoxy-2-methylpropane, from the viewpoint of easily suppressing the decrease in discharge capacity during storage of the zinc battery and easily obtaining excellent high-rate discharge performance.

[0048] Examples of the ether compound include crown ether compounds such as 18-crown-6, 15-crown-5, 12-crown-4, dibenzo-18-crown-6, dicyclohexano-18-crown-6, and dibenzo-24-crown-8; polyalkylene glycols such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; and glycerin. Examples of the ether compound include polyether compounds. From the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance, the oxygen-containing compound preferably contains an ether compound having a heterocycle containing an ether group, and more preferably contains 18-crown-6.

[0049] The number of ether groups in the ether compound is 1 or more, and from the viewpoint of easily suppressing a decrease in discharge capacity during storage of the zinc battery and easily obtaining excellent high-rate discharge performance, the following ranges are preferable: The number of ether groups is preferably 2 or more, 3 or more, 4 or more, 5 or more, or 6 or more; The number of ether groups is preferably 10 or less, 9 or less, 8 or less, 7 or less, or 6 or less.

[0050] The molecular weight of the oxygen-containing compound is preferably 50 or more, 70 or more, 80 or more, 100 or more, 120 or more, 150 or more, 160 or more, 170 or more, or 180 or more, from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance. The molecular weight of the oxygen-containing compound is preferably 2000 or less, 1500 or less, 1300 or less, 1200 or less, 1000 or less, 800 or less, or 600 or less, from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance. From these viewpoints, the molecular weight of the oxygen-containing compound is preferably 50 to 2000. The molecular weight of the oxygen-containing compound may be 190 or more, 200 or more, 210 or more, 220 or more, 240 or more, 260 or more, 300 or more, 340 or more, 350 or more, 400 or more, 450 or more, or 500 or more. The molecular weight of the oxygen-containing compound may be 500 or less, 400 or less, 350 or less, 340 or less, 320 or less, 300 or less, 280 or less, 270 or less, 260 or less, 250 or less, 230 or less, 220 or less, 210 or less, 200 or less, 190 or less, or 185 or less.

[0051] As the oxygen-containing compound, it is preferable to use a compound that is highly soluble in the electrolyte. Even if the compound is not highly soluble, it can be used by removing the residue by filtration, etc. The electrolyte according to the present embodiment does not need to contain alcohol.

[0052] The content of the oxygen-containing compound in the electrolyte is preferably in the following range based on the total amount of the electrolyte. The content of the oxygen-containing compound is preferably 0.1 mass% or more, 0.3 mass% or more, 0.5 mass% or more, 0.8 mass% or more, or 1 mass% or more from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance. The content of the oxygen-containing compound is preferably 5 mass% or less, 4.5 mass% or less, 4 mass% or less, 3.5 mass% or less, or 3 mass% or less from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance. From these viewpoints, the content of the oxygen-containing compound is preferably 0.1 to 5 mass%. The content of the oxygen-containing compound is preferably 1.2 mass% or more, 1.5 mass% or more, 1.8 mass% or more, 2 mass% or more, 2.2 mass% or more, 2.5 mass% or more, 2.7 mass% or more, or 3 mass% or more from the viewpoint of further easily suppressing the decrease in discharge capacity when the zinc battery is stored. The content of the oxygen-containing compound may be 3.5% by mass or more, 4% by mass or more, 4.5% by mass or more, or 5% by mass or more. From the viewpoint of easily obtaining even better high-rate discharge performance, the content of the oxygen-containing compound is preferably 2.7% by mass or less, 2.5% by mass or less, 2.2% by mass or less, 2% by mass or less, 1.7% by mass or less, 1.5% by mass or less, 1.2% by mass or less, or 1% by mass or less. The content of the oxygen-containing compound may be less than 0.5 mol / L based on the total amount of the electrolyte.

[0053] The content of the oxygen-containing compound is preferably in the following range relative to 1 part by mass of the surfactant. The content of the oxygen-containing compound is preferably 10 parts by mass or more, 30 parts by mass or more, 50 parts by mass or more, 80 parts by mass or more, or 100 parts by mass or more from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance. The content of the oxygen-containing compound is preferably 1000 parts by mass or less, 800 parts by mass or less, 600 parts by mass or less, 500 parts by mass or less, 450 parts by mass or less, 400 parts by mass or less, 350 parts by mass or less, or 300 parts by mass or less from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance. From these viewpoints, the content of the oxygen-containing compound is preferably 10 to 1000 parts by mass. The content of the oxygen-containing compound is preferably 150 parts by mass or more, 200 parts by mass or more, 250 parts by mass or more, or 300 parts by mass or more from the viewpoint of further suppressing the decrease in discharge capacity when the zinc battery is stored. The content of the oxygen-containing compound may be 350 parts by mass or more, 400 parts by mass or more, 450 parts by mass or more, or 500 parts by mass or more. The content of the oxygen-containing compound is preferably 250 parts by mass or less, 200 parts by mass or less, 150 parts by mass or less, or 100 parts by mass or less.

[0054] The content of the oxygen-containing compound is preferably in the following range relative to 100 parts by mass of the alkali metal hydroxide. The content of the oxygen-containing compound is preferably 1 part by mass or more, 1.5 parts by mass or more, 2 parts by mass or more, 2.5 parts by mass or more, or 3 parts by mass or more from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance. The content of the oxygen-containing compound is preferably 30 parts by mass or less, 25 parts by mass or less, 20 parts by mass or less, 16 parts by mass or less, 15 parts by mass or less, 13 parts by mass or less, 12 parts by mass or less, or 10 parts by mass or less from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance. From these viewpoints, the content of the oxygen-containing compound is preferably 1 to 30 parts by mass. The content of the oxygen-containing compound is preferably 4 parts by mass or more, 5 parts by mass or more, 6 parts by mass or more, 7 parts by mass or more, 8 parts by mass or more, or 9 parts by mass or more from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored. The content of the oxygen-containing compound may be 10 parts by mass or more, 12 parts by mass or more, 13 parts by mass or more, 15 parts by mass or more, or 16 parts by mass or more. From the viewpoint of easily obtaining further excellent high-rate discharge performance, the content of the oxygen-containing compound is preferably 9 parts by mass or less, 8 parts by mass or less, 7 parts by mass or less, 6 parts by mass or less, 5 parts by mass or less, or 4 parts by mass or less.

[0055] The electrolyte according to this embodiment can contain a liquid medium such as water (for example, ion-exchanged water).

[0056] Hereinafter, a nickel-zinc battery will be described as an example of a zinc battery in which the electrolytic solution according to the above embodiment is used.

[0057] The zinc battery according to the present embodiment includes, for example, a battery case, an electrode group (for example, a plate group) and an electrolyte solution housed in the battery case. The zinc battery according to the present embodiment may be either chemically formed or unchemically formed.

[0058] The electrode group includes, for example, a positive electrode (for example, a positive electrode plate), a negative electrode (for example, a negative electrode plate), and a separator. The positive electrode and the negative electrode are adjacent to each other via one or more separators. That is, one or more separators are provided between adjacent positive electrodes and negative electrodes. The electrode group may include multiple positive electrodes, negative electrodes, and separators. When the electrode group includes multiple positive electrodes and / or multiple negative electrodes, the positive electrodes and the negative electrodes may be alternately stacked with the separators interposed therebetween. The multiple positive electrodes and the multiple negative electrodes may be connected to each other, for example, by straps.

[0059] In the zinc battery according to the present embodiment, the negative electrode has a negative electrode current collector and a negative electrode material (electrode material) supported by the current collector. The negative electrode may be either before or after chemical formation.

[0060] The negative electrode current collector constitutes a conductive path for the current from the negative electrode material. The negative electrode current collector has, for example, a flat plate shape, a sheet shape, or the like. The negative electrode current collector may be a three-dimensional mesh-structured current collector constituted by foam metal, expanded metal, punching metal, felt-like material of metal fiber, or the like. The negative electrode current collector is constituted by a material having electrical conductivity and alkali resistance. For example, a material that is stable even at the reaction potential of the negative electrode (a material having an oxidation-reduction potential more noble than the reaction potential of the negative electrode, a material that forms a protective film such as an oxide film on the surface of the substrate in an alkaline aqueous solution to stabilize it, etc.) can be used as such a material. In addition, in the negative electrode, a decomposition reaction of the electrolyte proceeds as a side reaction to generate hydrogen gas, and a material with a high hydrogen overvoltage is preferable in that it can suppress the progress of such a side reaction. Specific examples of materials that constitute the negative electrode current collector include zinc; lead; tin; and metal materials (copper, brass, steel, nickel, etc.) plated with metals such as tin.

[0061] The negative electrode material is, for example, layered. That is, the negative electrode may have a negative electrode material layer. The negative electrode material layer may be formed on a negative electrode current collector. When the part of the negative electrode current collector that supports the negative electrode material has a three-dimensional mesh structure, the negative electrode material may be filled between the meshes of the current collector to form a negative electrode material layer.

[0062] The negative electrode material contains a negative electrode active material (electrode active material) containing zinc. Examples of the negative electrode active material include metallic zinc, zinc oxide, and zinc hydroxide. The negative electrode active material may contain one of these components alone, or may contain a plurality of types. The negative electrode material contains, for example, metallic zinc in a fully charged state, and contains zinc oxide and zinc hydroxide in an end-of-discharge state. The negative electrode active material is, for example, in a particulate form. That is, the negative electrode material may contain at least one selected from the group consisting of metallic zinc particles, zinc oxide particles, and zinc hydroxide particles. The content of the negative electrode active material is, for example, 50 to 95 mass% based on the total mass of the negative electrode material.

[0063] The negative electrode material may contain an additive. Examples of the additive include a binder. Examples of the binder include polytetrafluoroethylene, hydroxyethyl cellulose, polyethylene oxide, polyethylene, and polypropylene. The content of the binder may be, for example, 0.5 to 10 parts by mass with respect to 100 parts by mass of the negative electrode active material.

[0064] The positive electrode includes, for example, a positive electrode current collector and a positive electrode material supported on the positive electrode current collector. The positive electrode may be in a state before or after chemical formation.

[0065] The positive electrode current collector constitutes a conductive path for the current from the positive electrode material. The positive electrode current collector has, for example, a flat plate shape, a sheet shape, or the like. The positive electrode current collector may be a three-dimensional mesh-structured current collector constituted by foamed metal, expanded metal, punched metal, felt-like material of metal fiber, or the like. The positive electrode current collector is constituted by a material having electrical conductivity and alkali resistance. For example, a material that is stable even at the reaction potential of the positive electrode (a material having an oxidation-reduction potential more noble than the reaction potential of the positive electrode, a material that forms a protective film such as an oxide film on the substrate surface in an alkaline aqueous solution to stabilize it, etc.) can be used as such a material. In addition, in the positive electrode, a decomposition reaction of the electrolyte proceeds as a side reaction to generate oxygen gas, and a material with a high oxygen overvoltage is preferable in that it can suppress the progress of such a side reaction. Specific examples of materials that constitute the positive electrode current collector include platinum; nickel (foamed nickel, etc.); and metal materials (copper, brass, steel, etc.) plated with a metal such as nickel. Among these, a positive electrode current collector constituted by foamed nickel is preferably used. From the viewpoint of further improving the high rate discharge performance, it is preferable that at least the portion of the positive electrode current collector that supports the positive electrode material (positive electrode material supporting portion) is made of foamed nickel.

[0066] The positive electrode material is, for example, layered. That is, the positive electrode may have a positive electrode material layer. The positive electrode material layer may be formed on a positive electrode current collector. When the positive electrode material support part of the positive electrode current collector has a three-dimensional mesh structure, the positive electrode material may be filled between the meshes of the current collector to form the positive electrode material layer.

[0067] The positive electrode material contains a positive electrode active material (electrode active material) containing nickel. Examples of the positive electrode active material include nickel oxyhydroxide (NiOOH) and nickel hydroxide. The positive electrode material contains, for example, nickel oxyhydroxide in a fully charged state and nickel hydroxide in an end-of-discharge state. The content of the positive electrode active material may be, for example, 50 to 95 mass% based on the total mass of the positive electrode material.

[0068] The positive electrode material may further contain other components as additives other than the positive electrode active material, such as a binder, a conductive agent, and an expansion inhibitor.

[0069] Examples of the binder include hydrophilic or hydrophobic polymers. Specifically, for example, carboxymethyl cellulose (CMC), hydroxyethyl cellulose (HEC), hydroxypropyl methyl cellulose (HPMC), sodium polyacrylate (SPA), fluorine-based polymers (polytetrafluoroethylene (PTFE), etc.) can be used as the binder. The content of the binder is, for example, 0.01 to 5 parts by mass with respect to 100 parts by mass of the positive electrode active material.

[0070] The conductive agent may be a cobalt compound (metallic cobalt, cobalt oxide, cobalt hydroxide, etc.), etc. The content of the conductive agent is, for example, 1 to 20 parts by mass with respect to 100 parts by mass of the positive electrode active material.

[0071] The expansion inhibitor may be zinc oxide, etc. The content of the expansion inhibitor is, for example, 0.01 to 5 parts by mass with respect to 100 parts by mass of the positive electrode active material.

[0072] The separator may be, for example, a separator having a shape such as a flat plate or a sheet. Examples of the separator include a polyolefin-based microporous membrane, a nylon-based microporous membrane, an oxidation-resistant ion-exchange resin membrane, a cellophane-based regenerated resin membrane, an inorganic-organic separator, and a polyolefin-based nonwoven fabric. The separator may be processed into a bag shape so that the positive electrode and / or the negative electrode can be accommodated. In this case, the positive electrode and / or the negative electrode may be accommodated in the separator. The separator may be used alone or in combination of two or more types.

[0073] The manufacturing method of the nickel-zinc battery described above includes, for example, a component manufacturing process for obtaining components of the zinc battery, and an assembly process for assembling the components to obtain the zinc battery. In the component manufacturing process, at least electrodes (positive and negative electrodes) are obtained.

[0074] The electrodes can be obtained, for example, by adding a solvent (e.g., water) to raw materials of electrode materials (positive electrode material and negative electrode material) and kneading them to obtain an electrode material paste (a paste-like electrode material), and then forming an electrode material layer using the electrode material paste.

[0075] The raw materials for the positive electrode material include raw materials for the positive electrode active material (e.g., nickel hydroxide), additives (e.g., the binder), etc. The raw materials for the negative electrode material include raw materials for the negative electrode active material (e.g., metallic zinc, zinc oxide, and zinc hydroxide), additives (e.g., the binder), etc.

[0076] As a method for forming the electrode material layer, for example, an electrode material paste may be applied or filled onto a current collector, and then dried to obtain an electrode material layer. The density of the electrode material layer may be increased by pressing or the like, as necessary.

[0077] In the assembly process, for example, the positive and negative electrodes obtained in the component manufacturing process are alternately stacked with separators between them, and then the positive and negative electrodes are connected to each other with straps to form an electrode group. Next, this electrode group is placed in a battery case, and a lid is attached to the top of the battery case to obtain an unformed zinc battery (nickel-zinc battery).

[0078] Next, the electrolyte according to the present embodiment is poured into the battery case of the unformed zinc battery, and then left for a certain period of time. Then, the zinc battery (nickel-zinc battery) is obtained by forming the battery by charging under a predetermined condition. The forming conditions can be adjusted according to the properties of the electrode active materials (positive and negative active materials).

[0079] The above describes an example of a nickel-zinc battery (e.g., a nickel-zinc secondary battery) in which the positive electrode is a nickel electrode, but the zinc battery may also be an air-zinc battery (e.g., an air-zinc secondary battery) in which the positive electrode is an air electrode, or a silver-zinc battery (e.g., a silver-zinc secondary battery) in which the positive electrode is a silver oxide electrode.

[0080] The air electrode of the air zinc battery can be a known air electrode used in air zinc batteries. The air electrode includes, for example, an air electrode catalyst, an electron conductive material, etc. The air electrode catalyst can be an air electrode catalyst that also functions as an electron conductive material.

[0081] As the air electrode catalyst, one that functions as a positive electrode in an air zinc battery can be used, and various air electrode catalysts that can utilize oxygen as a positive electrode active material can be used. Examples of the air electrode catalyst include carbon-based materials (graphite, etc.) having an oxidation-reduction catalytic function, metal materials (platinum, nickel, etc.) having an oxidation-reduction catalytic function, and inorganic oxide materials (perovskite-type oxides, manganese dioxide, nickel oxide, cobalt oxide, spinel oxide, etc.) having an oxidation-reduction catalytic function. The shape of the air electrode catalyst is not particularly limited, and may be, for example, particulate. The amount of the air electrode catalyst used in the air electrode may be 5 to 70 volume % relative to the total volume of the air electrode, 5 to 60 volume %, or 5 to 50 volume %.

[0082] As the electron conductive material, a material that has electrical conductivity and enables electron conduction between the air electrode catalyst and the separator can be used. Examples of the electron conductive material include carbon blacks such as ketjen black, acetylene black, channel black, furnace black, lamp black, and thermal black; graphites such as natural graphite such as flake graphite, artificial graphite, and expanded graphite; conductive fibers such as carbon fibers and metal fibers; metal powders such as copper, silver, nickel, and aluminum; organic electron conductive materials such as polyphenylene derivatives; and any mixtures thereof. The shape of the electron conductive material may be particulate or may be other shapes. The electron conductive material is preferably used in a form that provides a continuous phase in the thickness direction in the air electrode. For example, the electron conductive material may be a porous material. The electron conductive material may also be in the form of a mixture or complex with the air electrode catalyst, and may be an air electrode catalyst that also functions as an electron conductive material as described above. The amount of the electronically conductive material used in the air electrode may be 10 to 80% by volume, 15 to 80% by volume, or 20 to 80% by volume relative to the total amount of the air electrode.

[0083] As the silver oxide electrode of the silver-zinc battery, a known silver oxide electrode used in silver-zinc batteries can be used. The silver oxide electrode includes, for example, silver(I) oxide. EXAMPLES

[0084] The present invention will be described in detail below with reference to examples, although the present invention is not limited to the following examples.

[0085] <Preparation of electrolyte> (Examples 1 to 12 and Comparative Examples 1 to 2) An electrolyte solution (potassium hydroxide concentration: 30 mass %, lithium hydroxide concentration: 1 mass %, additive content: the content shown in Table 1) was prepared by mixing ion-exchanged water, potassium hydroxide (KOH), lithium hydroxide (LiOH), and additives (surfactants and / or oxygen-containing compounds) shown in Table 1 below.

[0086] As the nonionic surfactant, polyoxyethylene octylphenyl ether (TritonX-100, manufactured by Sigma-Aldrich Japan LLC) was used. As the anionic surfactant, polyoxyethylene alkyl ether phosphate ester (mixture of monoester and diester) (manufactured by SOLVEY Co., Ltd., product name: RHODAFAC RA-600) was used. As the cationic surfactant, tetradecyltrimethylammonium bromide (special grade reagent, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used.

[0087] Comparative Example 3 An electrolyte solution (potassium hydroxide concentration: 30 mass %, lithium hydroxide concentration: 1 mass %) was prepared by mixing ion-exchanged water, potassium hydroxide (KOH), and lithium hydroxide (LiOH).

[0088] <Preparation of positive electrode> A lattice body made of foamed nickel with a porosity of 95% was prepared, and the lattice body was pressure-molded to obtain a positive electrode current collector. Next, a predetermined amount of cobalt-coated nickel hydroxide powder, metal cobalt, cobalt hydroxide, yttrium oxide, CMC, PTFE, and ion-exchanged water were weighed and mixed, and the mixture was stirred to prepare a positive electrode material paste. At this time, the mass ratio of the solid content was adjusted to "nickel hydroxide: metal cobalt: yttrium oxide: cobalt hydroxide: CMC: PTFE = 88: 10.3: 1: 0.3: 0.3: 0.1". The moisture content of the positive electrode material paste was adjusted to 27.5 mass% based on the total mass of the positive electrode material paste. Next, the positive electrode material paste was applied to the positive electrode material support part of the positive electrode current collector, and then dried at 80 ° C. for 30 minutes. After that, pressure molding was performed with a roll press to obtain an unformed positive electrode having a positive electrode material layer.

[0089] <Preparation of negative electrode> A tin-plated steel plate punching metal with an aperture ratio of 60% was prepared as a negative electrode current collector. Next, zinc oxide, metal zinc, HEC and ion-exchanged water were weighed and mixed in a predetermined amount, and the resulting mixture was stirred to prepare a negative electrode material paste. At this time, the mass ratio of the solid contents was adjusted to "zinc oxide:metal zinc:HEC=85:11.5:3.5". AV-15F (product name) manufactured by Sumitomo Seika Chemicals Co., Ltd. was used as the HEC. The moisture content of the negative electrode material paste was adjusted to 32.5 mass% based on the total mass of the negative electrode material paste. Next, the negative electrode material paste was applied onto the negative electrode current collector, and then dried at 80°C for 30 minutes. After that, it was pressure-molded by a roll press to obtain an unformed negative electrode having a negative electrode material (negative electrode material layer).

[0090] <Preparing the separator> For the separator, UP3355 (manufactured by Ube Industries, Ltd., product name, air permeability: 440 sec / 100 mL) was used as the microporous membrane, and nonwoven fabric (manufactured by Nippon Kodoshi Kogyo Co., Ltd., product name: VL-100, air permeability: 0.3 sec / 100 mL) was used as the nonwoven fabric. The microporous membrane was hydrophilized with a surfactant Triton-X100 (manufactured by Sigma-Aldrich Japan LLC) before the battery was assembled. The hydrophilization was performed by immersing the microporous membrane in an aqueous solution containing 1% by mass of Triton-X100 for 24 hours, and then drying at room temperature for 1 hour. The air permeability of the microporous membrane indicates the value after the hydrophilization. Furthermore, the microporous membrane was cut to a predetermined size, folded in half, and processed into a bag shape by heat welding the sides. The nonwoven fabric was cut to a predetermined size.

[0091] <Preparation of nickel-zinc battery> A positive electrode (unformed positive electrode) and a negative electrode (unformed negative electrode) were housed in a microporous membrane processed into a bag shape. After laminating the positive electrode housed in the bag-shaped microporous membrane, the negative electrode housed in the bag-shaped microporous membrane, and the nonwoven fabric, the electrode plates of the same polarity were connected with a strap to prepare an electrode group (electrode plate group). The electrode group was configured with two positive electrodes and three negative electrodes, with one nonwoven fabric placed between each of the positive and negative electrodes (between the microporous membrane on the positive electrode side and the microporous membrane on the negative electrode side). After placing this electrode group in a battery case, a lid was attached to the top of the battery case, and the above electrolyte was poured into the battery case to obtain an unformed nickel-zinc battery. Thereafter, charging was performed under conditions of 32 mA and 15 hours to prepare a nickel-zinc battery with a nominal capacity of 320 mAh.

[0092] <Evaluation of battery characteristics> Using the nickel-zinc batteries of the above-mentioned Examples and Comparative Examples, constant voltage charging of 320 mA (1C) and 1.9 V (charging was terminated when the current value decayed to 16 mA (0.05 C)) was performed in an environment of 25°C, and then constant current discharging of 64 mA (0.2 C) was performed until the battery voltage reached 1.1 V, and the discharge capacity A (initial capacity of low-rate discharge) was measured.

[0093] The nickel-zinc batteries of the above-mentioned Examples and Comparative Examples were stored at 40° C. for 28 days, and then left to stand for 3 hours at 25° C. Using the nickel-zinc batteries, in an environment of 25° C., constant voltage charging of 320 mA (1C) and 1.9 V (charging was terminated when the current value decayed to 16 mA (0.05 C)) was performed, and then constant current discharging of 64 mA (0.2 C) was performed until the battery voltage reached 1.1 V, and discharge capacity B (capacity after storage) was measured.

[0094] Using the nickel-zinc battery of the above-mentioned embodiment, a constant voltage charge of 320 mA (1C) and 1.9 V (charging was terminated when the current value decayed to 16 mA (0.05 C)) was performed in an environment of 25°C, and then a constant current discharge of 3200 mA (10C) was performed until the battery voltage reached 1.1 V, and the discharge capacity C (initial capacity of high-rate discharge) was measured.

[0095] For the Examples and Comparative Examples, the discharge capacity ratio B / A (unit: %) of discharge capacity B (after storage) to discharge capacity A (initial (before storage)) was calculated as the discharge capacity retention rate in the storage test. For the Examples, the discharge capacity ratio C / A (unit: %) of discharge capacity C (high rate discharge: 10C) to discharge capacity A (low rate discharge: 0.2C) was calculated as the discharge capacity ratio in the initial high rate discharge test. The results are shown in Table 1.

[0096] [Table 1]

Claims

1. The composition contains an alkali metal hydroxide, a surfactant, and an organic compound containing an oxygen atom, the organic compound has at least one group selected from the group consisting of a carboxy group and an ether group, The content of the organic compound is 10 parts by mass or more per 1 part by mass of the surfactant.

2. A method for preparing a coating composition comprising: an alkali metal hydroxide; a surfactant; and an organic compound containing an oxygen atom; the organic compound has at least one group selected from the group consisting of a carboxy group and an ether group, The electrolyte for a zinc battery, wherein the organic compound comprises a sugar.

3. 3. The zinc battery electrolyte according to claim 1, wherein the alkali metal hydroxide comprises potassium hydroxide.

4. The zinc battery electrolyte according to any one of claims 1 to 3, wherein the surfactant comprises a nonionic surfactant.

5. The zinc battery electrolyte according to any one of claims 1 to 4, wherein the surfactant comprises an anionic surfactant.

6. The zinc battery electrolyte according to any one of claims 1 to 5, wherein the surfactant comprises a cationic surfactant.

7. The zinc battery electrolyte according to any one of claims 1 to 6, wherein the organic compound comprises at least one selected from the group consisting of glucose, maltose, and raffinose.

8. The zinc battery electrolyte according to any one of claims 1 to 7, wherein the organic compound comprises an ether compound having a heterocycle containing an ether group.

9. A zinc battery comprising a positive electrode, a negative electrode, and the zinc battery electrolyte according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Cathode electrolyte for alkaline zinc battery, preparation method and application thereof

    CN101969144A

  • Nickel-zinc battery

    CN111048846A

  • JP1974041833A

  • Nickel zinc battery

    JP1983126665A

  • Sealed alkaline zinc storage battery

    JP1995161376A